Pyrolysis temperature shapes biochar-mediated soil microbial communities and carbon-nitrogen metabolism - Ren, Guihong; Shi, Wentao; Li, Wenwen; Wang, Jinlong; Wang, Chunjuan; Zhao, Guiyun (Frontiers in Microbiology, 2025)
IntroductionBiochar derived from agricultural residues has potential to improve soil quality and regulate microbial communities, but its effect depends strongly on pyrolysis temperature.MethodsIn this study, biochar prepared from Flammulina velutipes residue at 200 °C, 300 °C, and 400 °C was applied to cucumber seedling cultivation to evaluate its influence on soil physicochemical properties, microbial community structure, and functional metabolism.ResultsResults showed that soil pH increased significantly with biochar addition, from 5.00 in the control to 6.17 at 400 °C, while soil organic matter reached the highest level in the 400 °C treatment (90.03 g·kg−1). Available phosphorus and potassium were also enhanced, with maximum values of 731.81 mg·kg−1 and 481.68 mg·kg−1, respectively. Seedling growth responded differently to pyrolysis temperatures: the 300 °C biochar treatment increased above-ground biomass to 0.18 g and total biomass to 0.214 g per plant, significantly higher than the control (0.124 g). Metagenomic sequencing revealed shifts in dominant microbial phyla, with Acidobacteriota enriched at higher temperatures, and alpha diversity indices (Chao1, ACE, Sobs) increased under 400 °C biochar. Functional analysis indicated that carbon metabolic genes (e.g., acetyl-CoA synthesis, TCA cycle) were optimized at moderate to high temperatures, whereas nitrogen metabolism showed divergent responses, with nitrate reduction favored at 300 °C and nitrite reduction at 400 °C. Regression analysis demonstrated a positive correlation between microbial diversity and carbon metabolism genes (R2 = 0.75), but a negative correlation with nitrogen metabolism genes (R2 = 0.56). Redundancy analysis further identified ammonium nitrogen, acid phosphatase, and catalase as key drivers of microbial community and functional gene structure.DiscussionOverall, these findings highlight that biochar from mushroom residue, particularly produced at 300–400 °C, improves soil fertility, regulates microbial community composition, and modulates carbon and nitrogen metabolic processes, thereby enhancing cucumber seedling growth.